Evidence for the decay B 0J/ψω and measurement of the relative branching fractions of Bs0 meson decays to J/ψή and J/ψή - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
First evidence of the B 0J/ψω decay is found and the B 0 sJ/ψη and B 0 sJ/ψή decays are studied using a dataset corresponding to an integrated luminosity of 1.0 fb -1 collected by the LHCb experiment in proton-proton collisions at a centre-of-mass energy of s=7 TeV. The branching fractions of these decays are measured relative to that of the B 0J/ψ decay: where the last uncertainty is due to the knowledge of fd/fs, the ratio of b-quark hadronization factors that accounts for the different production rate of B 0 and B 0 s mesons. The ratio of the branching fractions of B 0 sJ/ψή and B 0 sJ/ψη decays is measured to be. © 2012 CERN.